Studies on the effect of host's genotype on the murine intestinal microbiota, including development of a flow cytometric method - Vaahtovuo, Jussi (Turun yliopiston julkaisuja, 2004)
Abstract.
Keywords: Arthritis, Rheumatoid; Bacteria : chemistry; Chromatography, Gas; Fatty Acids : analysis; Feces : microbiology; Flow Cytometry; Genotype; Intestines : microbiology; Major Histocompatibility Complex; Nucleic Acid Hybridization; Polymerase Chain Reaction; Spondylarthropathies; bakteerit; mikrobit; perimä; suolisto; bakterier; mikrober; arvsmassa; tarmkanal